PWE-146 The impact of body mass index on gastrectomy in western patients:a meta-analysis. (22nd June 2015) - Puccetti, F; Chaudry, A; Venerus, A; Allum, W
Abstract : Introduction: Although the impact of BMI on postoperative outcomes after curative resection for gastric cancer has been assessed in many different studies worldwide there have been conflicting conclusions. This may be due to the heterogeneity of study populations and geographical location may be a confounding factor due to a lack of international consensus regarding multimodal treatment. The aim of this meta-analysis was to specifically evaluate western cohort studies concerning the influence of preoperative BMI on surgical and oncological outcomes after gastric resectional surgery for adenocarcinomas. Method: Between December 2014 and January 2015 a comprehensive electronic search was performed to identify western publications relating to BMI and outcomes following resectional surgery for gastric cancer. Articles that did not report preoperative BMI, post-oesophagectomy morbidity, early mortality and 5 years overall survival were excluded. The search was performed using the Pubmed search engine and the reference lists for each of the articles included was also reviewed in order to find any additional studies. A statistical analyses were performed using OpenMetaAnalyst software (Version 10.10). Results: Three hundred and fifteen records deriving from the electronic search were examined, 7 western publications were included with a total of 4535 patients. The Meta-analysis study population was stratified in groups according to preoperative BMI: 2535 patients with BMI < 25 kg/m 2 and 2003 patients with BMI > 25 kg/m 2 . A raised BMI was strongly associated with a 35–40% increase in the risk of postoperative complications such as anastomotic leakages and wound infections rates (p-value: 0.006 and 0.016 respectively). Although the difference did not reach statistical significance, BMI > 25 was also associated with abdominal infections (28% with a p-value of 0, 237), bleeding (32% and 0, 075), pulmonary (30% and 0.077), cardiac complications rate (33% and 0, 222). Furthermore, neither the risk of Early mortality nor 5 years Overall Survival were affected by difference in BMI. Conclusion: This meta-analysis demonstrates that in western series a raised BMI is associated with an increase in morbidity, namely anastomotic leakages and wound infections rates but this did not translate into early mortality or a reduction in long term survival. Whilst a raised BMI should not preclude multimodal treatment including surgical resection in Western patients, we would suggest it is important to mitigate risk by careful preoperative planning, optimisation and a low index of suspicion for anastomotic leakage postoperatively. The increased risk of postoperative morbidity also has resource implications and further studies are required to analysed the cost-effectiveness of gastric surgery in high BMI patients. Disclosure of interest: None Declared.